Menciptakan Sekolah Ramah Anak Melalui Program Sosialisasi Edukatif Pencegahan Perundungan Di Taman Kanak-Kanak Negeri Pembina Kandis - Irasari Irasari; Mursida Mursida; Wan Azura; Mesis Rawati; Syaparudin BS; Candra Kirana (EL-EMIR INSTITUTE, 2026)
This Community Service activity aims to enhance early childhood understanding of bullying prevention at TK Negeri Pembina Kandis by instilling values ​​of mutual respect and care, as well as fostering the ability to resolve conflicts positively. The activity was implemented through educational outreach using an interactive learning approach that utilized various media—such as books, props, and educational videos—alongside activities involving Quran recitation, singing, and storytelling. Additionally, discussions were held with teachers and the school principal to gather information regarding the implementation of character education and the prevalence of bullying at the school. The results indicate that the applied methods successfully created a fun learning atmosphere, making it easier for children to grasp anti-bullying values. Discussion findings revealed that no cases of bullying have occurred at TK Negeri Pembina Kandis to date. Character and anti-bullying education have been consistently integrated into the learning process, helping children develop the habit of resolving issues independently, acknowledging their mistakes, and apologizing when they treat their peers poorly.